Differences in the detection of gastric premalignant conditions and its correlation with gastric cancer after a negative esophagogastroduodenoscopy in a low-risk gastric cancer country - Delgado-Guillena, Pedro Genaro; Morales-Alvarado, Víctor Jair; De-Riba-Soler, Beatriz; Llibre-Nieto, Gemma; Armas-Ramírez, Indira; Guillena-Castañeda, Terry; Levy-Ríos, Ivana; Jimeno-Ramiro, Mireya; Rigau-Cañardo, Joaquim; García-Rodríguez, Albert; Llargués Rocabruna, Esteve; Córdova, Henry; et al. (Revista de Gastroenterología del Perú, 2025)
Introduction: Gastric cancer (GC), with nearly 90% being sporadic adenocarcinomas, is preceded by gastric premalignant conditions (GPC). Accurate detection of GPC during esophagogastroduodenoscopy (EGD) can enhance the identification of high-risk patients and improve early GC diagnosis. However, GPC detection rates during EGD vary among endoscopists, potentially leading to differences in GC rates after a negative EGD (GC postEGD). Objective: This study aimed to assess the correlation between the GPC detection rate and the rate of GC post-EGD among endoscopists. Materials and methods: We conducted an observational study of EGDs at a community hospital between 2010 and 2019. GPC were defined as glandular atrophy, intestinal metaplasia, and dysplasia. EGDs were categorized into three groups: (i) benign, (ii) GPC, and (iii) malignant findings. GC post-EGD was defined as a diagnosis of gastric adenocarcinoma within three years of an EGD negative for malignancy. GPC detection rates and GC post-EGD were calculated for each endoscopist. Results: A total of 18,635 EGDs were performed by nine endoscopists. Gastric biopsies were obtained in 2,415 (13%) EGDs, identifying 533 GPCs (2.9%). The GC post-EGD rate was 1.26 per 1,000 EGDs. The detection rate of GPC varied between 1.8% and 5.8%, while GC post-EGD rates ranged from 0 to 3.36 per 1,000 EGDs. A negative correlation trend was observed between GC post-EGD and GPC detection rate (rs=-0.65, p=0.057), which was statistically significant for dysplasia (rs=-0.69, p=0.037). Conclusion: The detection rate of GPC—particularly dysplasia—showed a negative correlation with GC post-EGD in a community hospital within a low-risk setting during the period from 2010 to 2019.